PENGARUH MODEL PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP, SIKAP ILMIAH, DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS IV - Firdaus Dyah Utami; Ery Tri Djatmika; Cholis Sa’dijah (Graduate School of Universitas Negeri Malang, 2017)
This research aims to determine the effect of (1) learning models on the understanding concepts, scientific attitudes, and students' mathematical problem solving ability which are taught by guided inquiry model and conventional and (2) with different levels of motivation; (3) the interaction between learning model and learning motivation toward those variables. This research is a quasi experiment with non equivalent control group design. The sample is Fourth grade students at SDN Blimbing 01 which amounted to 76 students which determined by purposive sampling technique. The experimental class is Fourth grade students of IV A totaled 38 students , the same amount with the control class namely Fourth grade students of IV B. The data obtained were analyzed by using two-ways ANAVA. The results of the research are: (1) there is a effect of learning model on the three variables between the experimental class and the control class and (2) there is effect of with different learning motivation on the three variables; (3) there is no interaction between learning model and learning motivation toward those variables.Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran terhadap pemahaman konsep, sikap ilmiah, dan kemampuan pemecahahan masalah matematis (1) antara kelompok dengan model inkuiri terbimbing dan konvensional (2) dengan tingkat motivasi belajar yang berbeda; (3) interaksi antara model pembelajaran dan motivasi belajar terhadap variabel. Jenis penelitian ini adalah quasi eksperimen dengan desain non equivalent control grup. Sampel dalam penelitian ini adalah seluruh siswa kelas IV SDN Blimbing 01 yang berjumlah 76 siswa. Sampel dipilih melalui teknik sampel bertujuan. Kelas IV A berjumlah 38 siswa sebagai kelas eksperimen, dan kelas IV B berjumlah 38 siswa sebagai kelas control. Data dalam penelitian ini dianalisis dengan menggunakan two way ANAVA. Hasil penelitian ini, meliputi (1) ada pengaruhn model pembelajaran terhadap ketiga variabel antara kelas eksperimen dan kelas kontrol; (2) ada pengaruh motivasi belajar yang berbeda terhadap ketiga variabel; (3) tidak ada interaksi antara model pembelajaran dan motivasi belajar terhadap variabel tersebut.